The EU Structural Funds as a Means to hamper Migration - Peter Schmidt (European Regional Science Association (ERSA), 2012)
Comparing the economic development and current situation of the internal markets of the U.S. and the EU, two things are noticeable. On the one hand, the EU is conducting massive regional policy programmes (notably the Structural Funds) to foster economic cohesion among the 27 nations belonging to the Single European Market while in the U.S. with its 50 federal states such policies play a rather subordinate role. At the first glance, this seems to be consistent with the situation in this two markets because in the U.S. only 2% of the total population lives in regions with less than 75% of the US-average GDP per capita while in the EU approximately 31% of the total population lives in such regions eligible for structural funds support. In other words, regional policies in the U.S. would be redundant. But taking a closer look, on the other hand, reveals that the internal mobility of U.S. citizens is significantly higher than that of EU citizens. According to the neoclassical economic theory migration, besides the free flow of goods, services and capital, plays an important role in assuring convergence or economic cohesion, respectively. Following this strand of theory no regional policy is needed to achieve convergence among the regions or nations of a common market. Thus, comparing the two internal markets, the question comes up if the lower degree of economic cohesion in the EU has something to do with the lower internal market mobility of EU citizens and a higher degree of structural intervention of the EU regional policy? To answer this question, the paper consists of three parts. First, the theoretical background concerning migration and the potential need for regional policy is presented, to find out if one of them is a better instrument to achieve a balanced economic development within an internal market. In the second part, we discuss the actual situation of internal migration and examine why migration rates are comparatively low in the EU. In the last part, the interrelation between the EU regional policy and (internal) migration are analysed. Besides other things like language, culture or institutions this paper is going to argue that structural funds are inhibiting internal migration, which is one of the key measures in achieving convergence among the nations in the Single European market. It becomes clear, that the European regional policy aiming at economic cohesion among the 27 member states is inconsistent if the structural funds hamper instead of promoting migration.
Keywords: E62; F15; F22; 330; Migration; Structural Funds; European Integration